(untitled) (Revista Científica Compendium, 2020)
A teacher conception´s interpretation about self-knowledge is shown, to increase, cognoscitively and deeply, some ideas related to a pedagogical viewpoint from Physical Education in preschool-age children in daily motor practice to reach a healthy life. The researchers and two voluntarily involved preschool teachers´ world conception is not dogmatic. Everything shown was studied from the emergent interpretative paradigm, carried out with a phenomenological glance through recurrent interviews and observations. Scientific criteria and fiability merits were strengthened in transcript returning. Triangulation and narrative contrastings were also carried out. So, self-knowledge is made up of and interior capacity or sovereignty from the integral self to perceive, feel and understand idiosyncratic, conscious, lived reality with interaction in dignity with others in vital physical and spiritual shared spaces in the human evolutionary continuum of the thinking being who makes grounded decisions.